Value‐based health care in obstetrics. Issue 1 (13th June 2019) - Van Den Berg, Kim; Dijksman, Lea Magdalena; Keus, Samyra Hermione Jessica; Scheele, Fedde; Van Pampus, Maria Gabriel
Abstract: Rationale, Aims, and Objectives: We strive to maximize outcomes that are relevant to the women who deliver in our hospital. We demonstrate a practical method of using value‐based health care (VBHC) concepts to analyse how care can be improved. Method: Using International Consortium of Health Outcome Measurements (ICHOM) set, a practical outcome set was constructed for women who go into spontaneous labour at term of a singleton in cephalic presentation and used for benchmarking. We included data on interventions that are major drivers of outcomes. Data from two hospitals in Amsterdam and for The Netherlands for 2011 to 2015 were collected. Results: Benchmarking of readily available data helped identify a number of statistically significant and clinically relevant differences in obstetric outcomes. Caesarean section rate was significantly different at 13.7% in hospital 2 compared with 11.5% in hospital 1 with similar neonatal outcomes. Third and fourth degree tearing rates were significantly higher for hospital 1 at 5.5% compared with 3.6% for hospital 2 and the national average of 3.5%. On the basis of the guidelines, literature, and discussion, initiatives on how to improve these outcomes were then identified. These include caesarean section audit and guidelines regarding caesarean section decision making. In order to reduce the rate of third and fourth degree tearing, routine episiotomy on vaginal operative deliveries was introduced, and a training programme was set up to make care providers more aware of risk factors and potential preventive measures. Conclusion: Defining, measuring, and comparing relevant outcomes enable care providers to identify improvements. Collection and comparison of readily available data can provide insights in where care can be improved. Insights from literature and comparison of care practices and processes can lead to how care can be improved. Continuous monitoring of outcomes and expanding the set of outcomes that is readily available are key in the process towards value‐based care provision.